Green purchasing behaviour of international tourists in Malaysia using green marketing tools: theory of planned behaviour perspective. Issue 2 (18th January 2022) - Patwary, Ataul Karim; Mohamed, Muharis; Rabiul, Md Karim; Mehmood, Waqas; Ashraf, Muhammad Umair; Adamu, Adamu Abbas
Abstract : Purpose: This study aims to examine the effects of green marketing tools on tourists' behavioural intention to buy green products by measuring individuals' subjective norms, attitudes and perceived behavioural control. Design/methodology/approach: A total of 421 international tourists from several tourist attractions in Malaysia, selected through convenience sampling, participated in a survey. Findings: The analysis results using partial least squares structural equation modelling suggest that behavioural intention of international tourists is firmly influenced by attitude, perceived behavioural control, subjective norms and green marketing tools. However, the subjective norm does not work as a mediator. Practical implications: The relationships established in this study provide insight into hoteliers' knowledge for further implementation of green marketing strategies (eco-label, eco-brand, environmental advertising), which can enhance green attitudes and behavioural intention of purchasing green products in the hospitality industry. Originality/value: This study expands the theory of planned behaviour by including green marketing tools to measure international tourists' green buying tendency in Malaysia.